2021
DOI: 10.4322/bds.2021.e3104
|View full text |Cite
|
Sign up to set email alerts
|

Systemic versus local injection of bone marrow mesenchymal stem cells on 5-fluorouracil treated parotid glands of albino rats

Abstract: Objective: Head and neck cancer is the sixth leading cancer by incidence worldwide and eighth by death. Recent reports revealed that, not only radiotherapy but also chemotherapy may induce xerostomia. The aim of this study was to compare the possible regenerative effect of BMSCs through systemic and local injections. Material and Methods: 52 male Albino rats were randomly divided into 4 groups: Group 1: 10 rats received 0.5 ml of PBS by injection. Group 2: 14 rats received an intraperitoneal injection of 5-FU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The blood vessels showed dilatation and congestion with red blood cells. These results coincide with the results of previous studies that showed the effects of Cytarabine, 5-fluorouracil, and Cisplatin drugs on the submandibular salivary glands of rats (6), (11), (12) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The blood vessels showed dilatation and congestion with red blood cells. These results coincide with the results of previous studies that showed the effects of Cytarabine, 5-fluorouracil, and Cisplatin drugs on the submandibular salivary glands of rats (6), (11), (12) .…”
Section: Discussionsupporting
confidence: 92%
“…This period was chosen according to a previous comparative study that compared the therapeutic effect of systemically injected BMMSCs on the side effects of 5-Fluorouracil (chemotherapeutic drug) on the parotid glands after six and ten days. The statistical analysis showed a non-significant difference between the two groups with a p-value>0.05 (p-value=0.280) (11) .…”
Section: Discussionmentioning
confidence: 85%
“…Martin et al [44] stated that 5-FU affects DNA, RNA, and protein synthesis, and inhibits the secretion mechanism of the cells in the pancreas. Enlargement in aci- [2] in a histological and immunohistochemical study reported that 5-FU administration showed features of severe degenerative changes in parotid glands of the rats, which increased over time. 5-FU administration showed ill-defined acinar outline, multiple different sized vacuolization, and disfigured nuclear pattern.…”
Section: Discussionmentioning
confidence: 99%